Measurement of the branching fraction and Λ̄ polarization in B0→Λ̄pπ- - Aubert, B; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Garra Tico, J; Grauges, E; Martinelli, M; Palano, A; Pappagallo, M; et al. (2009)
We present a measurement of the B0→Λ̄pπ- branching fraction performed using the BABAR detector at the PEP-II asymmetric e+e- collider. Based on a sample of 467×106 BB̄ pairs we measure B(B0→Λ̄pπ-)=[3.07±0.31(stat)±0.23(syst)] ×10-6. The measured differential spectrum as a function of the dibaryon invariant mass m(Λ̄p) shows a near-threshold enhancement similar to that observed in other baryonic B decays. We study the Λ̄ polarization as a function of Λ̄ energy in the B0 rest frame (EΛ̄*) and compare it with theoretical expectations of fully longitudinally right-polarized Λ̄ at large EΛ̄*. © 2009 The American Physical Society.